Intuition as an Epistemological Foundation in Islamic Educational Management: A Systematic Literature Review - M. Fadli Al Azhari; Athok Fuadi (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2026)
This study aims to examine intuition as an epistemological foundation in Islamic educational management through a Systematic Literature Review (SLR) approach. This study is motivated by the dominance of rational-empirical approaches in educational management, which tend to ignore the intuitive dimension as a source of knowledge. However, in Islamic epistemology, intuition (irfani) holds equal standing with revelation (bayani) and reason (burhani). This study analyzed 25 articles published between 2010 and 2025 from the Scopus database and accredited national journals, with a selection process using the PRISMA framework. The results indicate that intuition, from an Islamic perspective, is an integrative form of knowledge, combining cognitive and spiritual dimensions. Intuition plays a crucial role in ethical decision-making, spiritual leadership, and innovation under conditions of uncertainty. However, its use cannot be separated from validation mechanisms through consideration, empirical data, and alignment with Islamic values ​​to avoid subjective bias. This study contributes by offering an integrative model that positions intuition as a structured epistemological component in Islamic educational management. These findings provide theoretical implications in the development of modern Islamic epistemology as well as practical implications for educational leaders in value-based decision making.